Evolving treatment modalities for immune thrombocytopenia in adults - Sushmita Khadka; Vineela Kasireddy; Pravash Kumar Dhakal; Chandrakala Dadiboyina (Greater Baltimore Medical Center, 2021)
The management of patients with relapsed or refractory immune thrombocytopenia (ITP) remains challenging for hematologists. While there are a multitude of drugs available, it is largely an individualized management based on patient preferences, side effects, previous treatment received, and responses to them, comorbidities and cost associated with the treatment. We hereby review the newer approaches in the treatment of ITP.